Organizational change management processes based on the project approach methodology - Степаненко, С. В. (My University, 2019)
The organizational change management paradigm currently lacks a common methodology for implementing them, and we hypothesize that project approach is one of the possible. The purpose of the study is to develop the main components of organizational change work in accordance with the methodology of the project approach. Using the methodology of the project approach, key provisions of organizational change management have been developed, the basis of which are the processes of forming a project product that reflects the purpose of organizational change, and the project management processes aimed at the effective implementation of the organizational change project. The main branches in the structural decomposition of the organizational change project work are the relevant knowledge areas, which include integration and content management, time and budget management, quality management, project personnel management, procurement management, risk management, communications management and stakeholders.
Keywords: organizational change management; organizational change; project management; risk management